Physicochemical and sensory evaluation of snack made with Parkia Speciosa (stink bean) - Saranya muthu (2022)
Because of the population's changing lifestyle nowadays, there has been a significant increase in fast foods and snacks consumption. People nowadays are expecting ready-to-eat food. Snacks were one of the ready-to-eat food. Snacks are an essential part of many people's daily nutrient and calorie intake. At the same time, consumers are expecting new flavor of snacks to consume. Parkia speciosa, also known as bitter beans, stink bean, or well known as "petal" among Malaysians, is usually served with dried sambal, chili peppers, red onions, and shrimps paste. Hence, this study aims to develop a snack made of P. speciosa. In this study, P. speciosa snacks were evaluated at different proportions (60%, 40%, and 20%). Snack prepared without P. speciosa was served as control. Physicochemical properties such as determination of colour and texture analyses ash, moisture, protein, and lipid, were analysed using the standard method. Results showed the moisture content of P. speciosa snack were ranged from 3.83% to 1.76%, ash ranged from 4.34% to 2.47% and protein ranged from 3.08% to 1.45%. The fat content varied from 63.89% to 88.7%, with the control having the highest fat level. On the other hand, the colour value of P. speciosa snacks showed significant changes when the amount of P. speciosa was decreased. As regard to sensory properties, formulation 2 snack had better acceptability. However, P. speciosa snack had higher nutritional value. Based on the results, novel P. speciosa snacks have been accepted by consumers. Key words: Parkia speciosa, physicochemical, sensory evaluation, development of snack, nutritional fact, flavor